Pengaruh Kecerdasan Emosional dan Komitmen Organisasional terhadap Kinerja Karyawan PT. NMM - Jean Rosalina Asthenu (P3M Politeknik Negeri Ambon, 2023)
Employee performance at PT. Nengmeypratama Malut Maluku (NMM) in carrying out work is decreasing. This is due to the lack of training in an effort to increase employee emotional intelligence and the lack of employee involvement in activities carried out by the company. This research aims to empirically test the influence of emotional intelligence on the performance of PT employees. NMM. The population in this study were all sales employees at PT. NMM, and the sample consisted of 30 people. The analytical tool used is simple linear regression analysis. The results of simple linear regression show that the significance value (sig) is 0.000, which means it is smaller than 0.05. Based on the research results, it shows that emotional intelligence and organizational commitment affect the performance of PT employees. NMM has a positive and significant effect. And the contribution of the influence of the variables emotional intelligence and organizational commitment to performance at PT. NMM was 25.7%, while the remaining 74.3% was influenced by other factors not studied. Improving employee performance at PT. NMM can be carried out by providing training to employees in an effort to increase their emotional intelligence and involving employees in company activities so that it is hoped that this will improve employee performance at work. Â Keywords: Emotional Intelligence; Organizational Commitment; Performance Â